Microbiological composition of untreated water during different weather conditions - Adna Bešić; Zarema Obradović; Arzija Pašalić; Amar Žilić (Journal of Health Sciences, 2011)
Introduction: Water can support the growth of different microorganisms which may result in contamination. Therefore, the microbiological examination is required for testing the hygienic probity of water. In the study of microbial composition of untreated, natural spring and mineral water differences in the presence and number of bacteria during the two periods, winter and summer, are detectable. Methods: In our study, we analyzed and compared the following parameters, specified in the Rulebook: total bacteria and total aerobic bacteria (ml/22 and 37°C), total Coliform bacteria and Coliforms of fecal origin (MPN/100ml), fecal streptococci as Streptococcus faecalis  (MPN/100ml), Proteus spp (MPN/100ml), and Pseudomonas aeruginosa (MPN/100 ml) Sulphoreducing Clostridia (cfu / ml). The paper is a retrospective study in which we processed data related to the period of 2005-2009 year. While working, we used the descriptive-analytical comparative statistical treatment. Results: The obtained results show statistically significant differences in the microbial composition of untreated water in the two observed periods, Conclusions: Findings were consequence of different weather conditions in these periods, which imply a number of other variable factors.